ENGLISH TEACHER PARTICIPANTS ENGAGEMENT IN ONLINE LEARNING SESSION OF TEACHING PROFESSION CERTIFICATION PROGRAM - Pius N. Prihatin (Sanata Dharma University Yogyakarta, 2018)
This research analyzes the engagement of English teachers who participated in the preparation of Teaching Profession Certification Program (TPCP/PLPG) in Sanata Dharma University. There were 70 English teachers from many schools in the Province of Central Java who participated in the online learning session before they follow the workshop session. The result of this analysis indicated that the level of active participation of the participants in the online learning session is very low. Although the mean score of the frequency of access (= 42.39) is above the expected frequency of access (24), the mean score of frequency of message (= 9.32) is far below the expected frequency of message (72). In addition, there are no significant differences between the engagement of male and female participants in both the frequency of access and the frequency of messages. Furthermore, the frequency of access indicates a weak correlation with the scores of final examination (r = 0.21, p .05), but the correlation between the frequency of access and the final examination scores does not significantly exist (r = 0.02, p .05). It is recommended that future attempts to carry out the online activities in professional development programs for English teachers should be focused on encouraging instructors and participants to be more engaged in the online learning environment.DOI: https://doi.org/10.24071/ijiet.2018.020201